Rancang Bangun Alat Deteksi Kebisingan Perpustakaan dengan Indikator Peringatan Berbasis Internet Of Things (IOT) - Yourman Doni Siddik; Akim Manaor Hara Pardede; Husnul Kahir (Repeater : Publikasi Teknik Informatika dan Jaringan, 2024)
Noise in libraries can disrupt the concentration and comfort of visitors who are reading or studying. Therefore, a tool is needed to detect noise and automatically issue warnings to maintain silence in the library environment. This research aims to design and develop a noise detection tool in libraries using Internet of Things (IoT) technology. The device consists of a sound sensor that detects noise levels and sends data to a cloud-based server for analysis. When the noise level exceeds a specified threshold, the tool provides warnings through visual indicators and notifications to the library staff. The prototype was tested in a library environment and was able to detect noise accurately and issue real-time alerts. The results showed that the device effectively reduced noise levels and improved the comfort of library visitors. With the implementation of IoT technology, this system can be accessed and monitored remotely, facilitating library management in maintaining a conducive environment.